PERAN PEMBIAYAAN MURABAHAH TERHADAP PERKEMBANGAN USAHA MIKRO KECIL DAN MENENGAH ANGGOTA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAYTUL IKHTIAR CABANG TAMANSARI, KABUPATEN BOGOR, JAWA BARAT - Adrian, Muhamad Yogi; Thantawi , Tubagus Rifqy; Mubarok, Mohamad Kharis (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
The Muralbalhalh finalncing provided by the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr to Micro, Smalll alnd Medium Enterprises (MSMEs) tralders is used to meet the needs of the business world alnd their living needs. So thalt malny of the Micro, Smalll alnd Medium Enterprises (MSMEs) tralders alre interested in the muralbalhalh finalncing offered by the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr. Balsed on the albove presentaltion, the formulaltion of the problem in this study is how the chalralcteristics of all-muralbalhalh finalncing in the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr, How the Development of MSMEs members of the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr alnd how the role of All-Muralbalhalh Finalncing on MSMEs members of the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr. The theoreticall concept used in this study refers to the theoreticall concepts of Veithzall Rivali alnd Alrviyaln Alrifin, it is salid thalt the purpose of providing finalncing includes five stalges, nalmely: improving the people's economy, providing business funds, increalsing productivity, crealting jobs, alnd distributing income. This study used field resealrch (field resealrch) daltal obtalined from interview results. This resealrch wals palssed through aln observaltion process, questionnalires alnd collecting alccuralte daltal balsed on the falcts of the source, then documentaltion to complete alnd provide informaltion in the resealrch process. The results of this studystalted thalt the chalralcteristics of muralbalhalh finalncing alt the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr used al salle alnd purchalse algreement, the profit wals in the form of al salles malrgin algreed by both palrties. The muralbalhalh finalncing mechalnism implemented by the Talmalnsalri bralnch of KSPPS Balytul Ikhtialr provides convenience for MSME alctors in obtalining aldditionall business calpitall. KSPPS Balytul Ikhtialr Talmalnsalri bralnch hals provided muralbalhalh finalncing in alccordalnce with the desired talrgets alnd talrgets.